Розвиток скляної промисловості в Україні: потенціал з урахуванням наявних викликів - Zaloznova, Yuliya S.; Petrova, Iryna P. (Institute of Industrial Economics of NAS of Ukraine, 2025)
The article provides a comprehensive analysis of the current state and future prospects of the glass industry in Ukraine, particularly in the context of energy efficiency, import substitution, and integration into the European economic area. Special attention is given to the dynamics of the flat glass market, especially considering the growing demand driven by urbanization, infrastructure development, and the concept of smart cities. The main factors contributing to the rising demand for innovative types of glass—such as energy-saving, solar-control, and smart glass—are analyzed, with emphasis on their application in construction, automotive manufacturing, and alternative energy.The article assesses the investment potential for building a flat glass manufacturing plant in Ukraine, taking into account opportunities for import substitution, reducing dependency on foreign suppliers, and enhancing the country’s export capacity. It explores the role of public-private partnerships in the development of eco-industrial parks, which help ease the fiscal burden and ensure sustainable regional economic development. It is determined that the implementation of an investment project in flat glass production is economically viable and has a significant social impact, including the creation of over 1,000 jobs, stimulation of related economic sectors, and increased tax revenues.The article substantiates the need for state support of such initiatives through financial programs, preferential loans, grants, and the adaptation of national legislation to European quality and energy efficiency standards. It also emphasizes the importance of these initiatives for the country’s economic recovery, diversification of industrial potential, and integration into the unified European economic space. The relevance of this project is reinforced by its high economic and social benefits, including the potential creation of a sectoral eco-industrial park, development of domestic scientific and production capacity, and enhancement of the national economy’s energy efficiency. The language of the article is Ukrainian.